Human ectoenzyme-expressing ILC3: immunosuppressive innate cells that are depleted in graft-versus-host disease - Hazenberg, Mette D. (Blood Adv, 2019)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is often associated with chemotherapy- and radiotherapy-induced host tissue damage, leading to graft-versus-host disease (GVHD). Innate lymphoid cells (ILC) have an essential role in tissue homeostasis and tissue repair via their production of interleukin (IL)-22, which acts on intestinal stem cells. The tissue healing capacities of ILC via IL-22 in the context of allo-HSCT and GVHD has previously been demonstrated in a mouse model for acute GVHD. We investigated potential other ways of ILC-mediated tissue protection against GVHD. Tissue injury leads to the release of danger-associated molecular patterns (DAMPs). DAMPs interact with purinergic receptors and ectoenzymes on immune cells and induce pleiotropic effects, including activation of proinflammatory antigen-presenting cells and immunosuppressive effects via the generation of adenosine. Here, we report a novel subset of human ILC3 that coexpress the ectoenzymes CD39 and CD73 (ecto(+) ILC3). Ecto(+) ILC3 express RORγt and were present in the oral-gastrointestinal tract and bone marrow. ILC3 ectoenzyme expression is modulated by the proinflammatory cytokine IL-1β. Extracellular adenosine triphosphate (eATP) stimulated ecto(+) ILC3 to produce IL-22 and adenosine. Activated ecto(+) ILC3 suppressed autologous T-cell proliferation in coculture experiments via the production of adenosine. In allo-HSCT recipients, intestinal GVHD was associated with reduced proportions of ecto(+) ILC3 and decreased levels of adenosine and its metabolite inosine. Taken together, ecto(+) ILC3 have immunosuppressive properties, but in patients with GVHD, ecto(+) ILC3 are depleted. A lack of ecto(+) ILC3 and subsequent reduced capacity to neutralize DAMPs may contribute to the development of GVHD.